Adult Learners Motivational Orientations And Motivation Towards Programme Of The Institute For The Studies In Islamic Sciences - Abdul Hamid, Mohd Halimi (1996)
Providers of continuing education for adult learners need a thorough understanding of adult learners needs which are basically different fro m those of younger learners . Therefore, it is crucial for them to comprehend the major motivational orientations and motivation affiliated to successful participation of adult learners in continuing education. The general objective of this study was to examine adult learners motivational orientations and motivation towards programmes of the Institute for the Studies in Islamic Sciences (Institut Pengajian Ilmu-ilmu Islam, IPI) . IPI is a provider of continuing education under the flagship of the Muslim Youth Movement of Malaysia (Angkatan Belia Islam Malaysia, ABIM) . Specifically, the study aimed to : l . identify the major motivational orientations of adult learners at IPI ; 2. determine the level of motivation of adult learners towards IPI programmes; 3 . determine the relationship between adult learners motivational orientations and motivation towards current courses with the socio demographic variables; 4. determine the relationship between adult learners motivational orientation sand motivation towards current courses ; and 5. determine if there are any significant differences in motivation towards current course amongst (a) respondents of different level of academic attainment, (b) respondents from different working sectors, and ( c) respondents from different category of services. The survey research method utilising a self-administered questionaire was used. A total of 126 adult learners of IPI from a total enrollment of 310 students were involved in the study.